2021
DOI: 10.1186/s12888-021-03511-9
|View full text |Cite
|
Sign up to set email alerts
|

The burden of caring for adults with depression and suicidal ideation in five large European countries: analysis from the 2020 National Health and Wellness Survey

Abstract: Background Suicidal ideation (SI) affects approximately 30–40% of those with major depressive disorder (MDD). To date, studies have examined the substantial humanistic and economic burden to caregivers of persons with MDD, however little is known of the impact of caring for persons with MDD when SI is present. This study examined the additional burden imposed on caregivers for persons with unipolar depression and SI in five major European countries. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Caregivers in this study also reported 46% overall activity impairment, with impairments of 44%, 43%, and 53% for caregivers of patients with TD and underlying SCZ, BD, and MDD, respectively. The overall activity impairment observed here for caregivers of patients with TD and MDD (53%) was greater than that recently reported for caregivers of patients with unknown TD status with MDD alone (40%), or MDD and suicidal ideation (49%) [ 30 ]. For each of the cited studies work impairment was assessed via WPAI, which is a standardized questionnaire for assessing work and activity impairment.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Caregivers in this study also reported 46% overall activity impairment, with impairments of 44%, 43%, and 53% for caregivers of patients with TD and underlying SCZ, BD, and MDD, respectively. The overall activity impairment observed here for caregivers of patients with TD and MDD (53%) was greater than that recently reported for caregivers of patients with unknown TD status with MDD alone (40%), or MDD and suicidal ideation (49%) [ 30 ]. For each of the cited studies work impairment was assessed via WPAI, which is a standardized questionnaire for assessing work and activity impairment.…”
Section: Discussioncontrasting
confidence: 74%
“…Caregivers of patients with TD and SCZ also reported greater impact on work absenteeism (12%) and presenteeism (42%) than previously reported for caregivers of patients with SCZ with unknown TD status (absenteeism, 5%; presenteeism, 25%) [ 37 ]. Likewise, caregivers of patients with TD and MDD reported higher levels of presenteeism (52%) and overall work impairment (57%) than previously reported for caregivers of patients with MDD without suicidal ideation (presenteeism, 35%; overall work impairment, 40%) [ 30 ]. Caregivers in this study also reported 46% overall activity impairment, with impairments of 44%, 43%, and 53% for caregivers of patients with TD and underlying SCZ, BD, and MDD, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Fourteen quantitative studies involving 12 cohorts were included (Borisonik & Kholmogorova, 2018; Cerel et al., 2006; Chessick et al., 2007, 2009; Chiang et al., 2015; Crasta et al., 2021; Jaffe et al., 2021; Katz et al., 2015; Kjellin & Östman, 2005; Lawn & McMahon, 2015; Magne‐Ingvar & Öjehagen, 1999a, 1999b; Maple et al., 2021; McDonell et al., 2003). Study designs included descriptive and analytical cross‐sectional studies with samples totalling 3705 carer participants (14 were bereaved by suicide).…”
Section: Resultsmentioning
confidence: 99%
“…Articles linked to the themes and subthemes are presented in Table 4. -Doku et al, 2017;Castelli Dransart & Guerry, 2017;Chessick et al, 2007Chessick et al, , 2009Dempsey et al, 2019;Fogarty et al, 2018;Giffin, 2008;Jaffe et al, 2021;Katz et al, 2015;Kjellin & Östman, 2005;Magne-Ingvar & Öjehagen, 1999b;Maple et al, 2021;McLaughlin et al, 2014McLaughlin et al, , 2016Nosek, 2008;Nygaard et al, 2019;Sellin et al, 2017;Spillane et al, 2020;Sun & Long, 2008;Talseth et al, 2001;Vandewalle et al, 2021;Wand et al, 2019;Wayland et al, 2021 Learning a new role Asare-Doku et al, 2017;Castelli Dransart & Guerry, 2017;Dempsey et al, 2019;Fogarty et al, 2018;Giffin, 2008;Magne-Ingvar & Öjehagen, 1999b;Nosek, 2008;Sellin et al, 2017;Spillane et al, 2020;Talseth et al, 2001;Vandewalle et al, 2021;Wand et al, 2019;Wayland et al, 2021 Own life on hold Asare-Doku et al, 2017;Castelli Dransart & Guerry, 2017;Dempsey et al, 2019;…”
Section: Themesmentioning
confidence: 99%
See 1 more Smart Citation